Are "normal hips" being labeled as femoroacetabular impingement due to EE angle?. Issue 13 (March 2017) - You, Tian; Yang, Bei; Zhang, Xin-tao; Jiang, Xiao-cheng; Wang, Shuang; Zhang, Wen-tao
Abstract : Abstract: Gluteal muscle contracture (GMC) is a clinical syndrome characterized by gait abnormality and limb dysfunction, as well as secondary deformities of pelvis and femur. Femoroacetabular impingement (FAI) typically could be diagnosed on the basis of computed tomography (CT) such as the equatorial-edge angle (EE angle), but it did not work well in GMC patients. In this study, we retrospected all image data and found small EE angles in GMCs, which meant retroverted acetabulum; however, none of them showed no symptoms and signs of FAI. Therefore, we had reasons to think that, some normal hips with unbalanced hip myodynamia as same as GMCs, may be incorrectly diagnosed as FAI through measuring EE angle only. In consequence, the paper was designed to assess the use of the EE angle in the assessment of FAI in the diagnosis, as described by Werner. Twenty-three patients (46 hips) were collected and calculated with the "equatorial-edge angle" (EE angle) by CT scans. All of them were excluded from FAI. Review of the hips showed a mean EE angle was 12.93°, with a minimum of -3.42° and a maximum of 24.08°. The mean value for males and females were 13.52° and 12.40°, respectively, without statistical significance, although the mean value of left hips and right sides reached 13.32° and 12.54° individually, not having statistical differences neither. There were not any symptoms or signs of FAI in all patients. Thus, the reduced EE angle could suggest the local excessive coverage of the femoral head by the anterior acetabular edge, but might not be a reasonably good predictor of FAI. GMC patient's acetabular deformity mainly manifests as increased retroversion, which may be the anatomical basis for FAI and lead to high risks of the acetabular impingement. However, all patients in this study showed no symptoms and signs of FAI, suggesting that the measurement of EE angle can only be applied to assessing those people with normal hip myodynamia, and the bone deformity and the muscular disorder should be both considered in the diagnosis of FAI.